Effect of body mass and melanism on heat balance in Liolaemus lizards of the goetschi clade - Moreno Azócar, Débora Lina (2016)
The body temperature of ectotherms depends on the environmental temperatures and behavioral adjustments, but morphology may also have an effect. Forexample, in colder environments, animals tend to be larger and to show higher thermal inertia, as proposed by Bergmann's rule and the heat balance hypothesis (HBH). Additionally, dark coloration increases solar radiation absorption and should accelerate heat gain (thermal melanism hypothesis, TMH). We tested Bergmann's rule, the HBH and the TMH within the Liolaemus goetschi lizard clade, which shows variability in body size and melanic coloration. We measured heating and cooling rates of live and euthanized animals, and tested how morphology and color affect these rates. Live organisms showless variable and faster heating rates compared with cooling rates, suggesting behavioral and/or physiological adjustments. Our results support Bergmann's rule and the HBH, as larger species show slower heating and cooling rates. However, we did not find a clear pattern to support the TMH. The influence of dorsal melanism on heating by radiation was masked by the body size effect in live animals, and results from euthanized individuals also showed no clear effects of melanism on heating rates. Comparison among three groups of live individuals with different degrees of melanism did not clarify the influence of melanism on heating rates.However, when euthanized animals fromthe same three groups were compared, we observed that darker euthanized animals actually heat faster than lighter ones, favoring the TMH. Although unresolved aspects remain, body size and coloration influenced heat exchange, suggesting complex thermoregulatory strategies in these lizards, probably regulated through physiology and behavior, which may allow these small lizards to inhabit harsh weather environments.